Law Enforcement Against Perpetrators of Narcotics Trafficking Cases (Case Study of Verdict Number 565/Pid.Sus/2024/PN.Tjk) - Anugrah, M. Iqbal; Seregig, I Ketut (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Law enforcement against perpetrators of narcotics crimes, especially in cases of narcotics trafficking, is a challenge for the criminal justice system. This study aims to analyze how law enforcement is carried out against perpetrators of narcotics trafficking cases and the judge's considerations in optimizing criminal sentences. The problem of this study is how law enforcement is carried out against perpetrators of narcotics trafficking cases and how judges consider optimizing criminal sentences against perpetrators of narcotics intermediary crimes to the maximum (Decision Number 565 / Pid.Sus / 2024 / PN.Tjk). The research method used in this study is through a normative legal approach and empirical legal approach using secondary and primary data. then qualitative legal analysis. The results of this thesis research can be concluded that law enforcement against perpetrators of narcotics trafficking cases in Indonesia is carried out strictly based on Law Number 35 of 2009 concerning Narcotics. Stages and aspects of law enforcement, namely Investigation and Investigation Conducted by the police (Bareskrim Polri), National Narcotics Agency (BNN), and related agencies. Using investigative techniques such as arrest operations, undercover operations, and monitoring illegal transactions. Judge's considerations In making a decision, the Defendant's actions have violated the law as stated in Law Number 35 of 2009 concerning narcotics, namely Any person who without rights or against the law offers to sell Class I Narcotics, shall be punished with life imprisonment or imprisonment of at least 5 (five) years and a maximum of 20 (twenty) years and a fine of at least IDR 1,000,000,000.00 (one billion rupiah) and a maximum of IDR 10,000,000,000.00 (ten billion rupiah). Suggestions submitted in this study include optimizing rehabilitation for narcotics users, strengthening coordination between law enforcement agencies, and increasing the use of technology in investigations and law enforcement.